2012
DOI: 10.1128/jb.01050-12
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Variation among Contemporary Pseudomonas aeruginosa Isolates from Chronically Infected Cystic Fibrosis Patients

Abstract: ABSTRACTThe airways of individuals with cystic fibrosis (CF) often become chronically infected with unique strains of the opportunistic pathogenPseudomonas aeruginosa. Several lines of evidence suggest that the infectingP. aeruginosa Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 49 publications
2
86
0
Order By: Relevance
“…Thus the P. aeruginosa WinCF responses may reflect the true physiology of this microbe and others like it in the CF lung and is in stark contrast to the physiology of the Attack Community during exacerbation events. However, P. aeruginosa exhibits large strain differentiation in the CF lungs (Chung et al, 2012;Klockgether et al, 2013), making conceptualizing the organism in the context of CF challenging. Also, while observed as a member of the Climax Community in the patient in this study, it cannot be inferred that P. aeruginosa has a limited role in all exacerbations.…”
Section: Sources Of the Fermentative Responsementioning
confidence: 99%
“…Thus the P. aeruginosa WinCF responses may reflect the true physiology of this microbe and others like it in the CF lung and is in stark contrast to the physiology of the Attack Community during exacerbation events. However, P. aeruginosa exhibits large strain differentiation in the CF lungs (Chung et al, 2012;Klockgether et al, 2013), making conceptualizing the organism in the context of CF challenging. Also, while observed as a member of the Climax Community in the patient in this study, it cannot be inferred that P. aeruginosa has a limited role in all exacerbations.…”
Section: Sources Of the Fermentative Responsementioning
confidence: 99%
“…The most Drug sequence influences evolution of resistance commonly mutated gene was fusA1, which encodes elongation factor G and was mutated in 11 different replicate lineages adapted to tobramycin. fusA1 has been observed to be mutated in clinical isolates of P. aeruginosa [39][40][41], as well as in adaptive evolution studies to aminoglycosides in P. aeruginosa [34] and E. coli [12,16,18]. Mutations in fusA1 may also contribute to altered intracellular (p)ppGpp levels, which may modulate virulence in P. aeruginosa [41].…”
Section: Genomic Mutations Of Adapted Lineagesmentioning
confidence: 99%
“…fusA1 has been observed to be mutated in clinical isolates of P. aeruginosa [39][40][41], as well as in adaptive evolution studies to aminoglycosides in P. aeruginosa [34] and E. coli [12,16,18]. Mutations in fusA1 may also contribute to altered intracellular (p)ppGpp levels, which may modulate virulence in P. aeruginosa [41]. Mutations in gyrA and gyrB were observed during ciprofloxacin evolution, but none were observed in parC and parE (the other genes of the quinolone resistance-determining region [29]).…”
Section: Genomic Mutations Of Adapted Lineagesmentioning
confidence: 99%
“…A recent study has suggested that a mixture of strains influenced traits such as drug response in ways that were difficult to predict from the study of single strains (9). Clinical isolates of P. aeruginosa, even from the same respiratory sample, can have striking differences in phenotypes, including colony morphology, quorum-sensing regulation, and motility (9)(10)(11)(12)(13), and recent data highlight that there is gene expression diversity even among phenotypically similar strains (9). Given the significant limitations of the aforementioned laboratory approaches, novel methods for directly interrogating population-level microbial gene expression in the CF lung are needed to provide accurate information about the growth and virulence of P. aeruginosa in the CF airway.…”
mentioning
confidence: 99%